The Role of Financial Technology in Enhancing Cloud Accounting Adoption in the Banking Sector: Evidence from Palestinian Banks - Raed Abueid; Kuat Ismanto; Mohammad Rosyada (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study aims to examine the role of financial technology (FinTech) in enhancing the adoption of cloud accounting within banks operating in Yatta City, Palestine. The research specifically investigates the influence of FinTech dimensions, including financial technology applications, digital platforms, and technological techniques, on the effectiveness of cloud accounting implementation in the banking sector. The study employed a quantitative research design using a structured questionnaire distributed to employees of Palestinian banks. A total of 28 valid responses were collected and analyzed using descriptive statistics and simple regression analysis to evaluate the relationship between FinTech adoption and cloud accounting practices. The findings indicate that the adoption of financial technology among Palestinian banks is relatively high, particularly in the use of digital banking applications, automated teller machines, and mobile banking services. Cloud accounting implementation was also perceived positively by employees, especially regarding accessibility, operational efficiency, data integration, and financial information security. Regression analysis revealed a statistically significant positive relationship between financial technology and cloud accounting adoption. Among the examined dimensions, financial technology applications showed the strongest influence, followed by technological techniques and digital platforms. This study contributes to the literature on digital transformation in banking by integrating FinTech and cloud accounting perspectives in a developing-country context. The findings provide practical insights for policymakers and banking institutions to strengthen digital accounting infrastructure, improve financial service delivery, enhance employee digital competencies, and invest in secure cloud-based financial systems to support sustainable banking innovation.